An Analysis of Village Governance With Organizational Commitment as a Moderating Variable - Vera Oktari; Ulfa Afifah (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
This study was conducted to examine the moderating effect of organizational commitment on the relationship between the government's internal control system, village financial management, and apparatus performance on village governance. The research plan is carried out for 10 (ten) months. This research will be conducted on the Village Government in Rokan Hilir Regency. Determination of the sample was determined by the purposive sampling method. Data was obtained by using a questionnaire. Data analysis will be carried out with quantitative data analysis. While the data is processed using Partial Least Square (PLS). The data analysis method in this study uses a structural equation model (SEM). The research data analysis that will be carried out is descriptive statistical analysis, statistical analysis, model measurement (outer model), and Partial Least Square (PLS) structural equation analysis, and hypothesis testing.